1998
DOI: 10.1038/sj.ijo.0800656
|View full text |Cite
|
Sign up to set email alerts
|

Leptin: its pharmacokinetics and tissue distribution

Abstract: OBJECTIVE: The pharmacokinetics and tissue distribution of leptin in rats was investigated. DESIGN: A catheter was inserted in the right jugular vein of rats on the day prior to experiment. The next day, blood was sampled and then a tracer dose of radioiodinated hormone was administered via the catheter. Thereafter, small (200 m ml) samples of blood were taken at regular intervals. Two experiments were conducted over different sampling times. TCA precipitated radioactivity was counted in samples of plasma and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
49
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 19 publications
11
49
0
4
Order By: Relevance
“…30 When these data were reanalyzed and modeled using the same approach employed in the current study, the calculated half-lives and mean residence times, although slightly less, were comparable to our results (Landt unpublished results). Similar values were obtained by Hill et al using a dose that was approximately 1a1000 of those used in the current study and in the study by Cumin et al 31 The shorter calculated half-lives observed in these studies may simply be attributable Table 2 Pharmacokinetic characteristics of recombinant met-human leptin when administered intraperitoneally (10 mgag body weight) to C57BLa6J mice fed a normal diet (n 6) or a high-fat diet (n 8) Leptin pharmacokinetics B Ahre Ân et al to a shorter sampling period, and hence the terminal elimination phase was de®ned by a minimal number of later time points. It is clear from comparing several different studies, using doses ranging over at least three orders of magnitude, that the rates of elimination and mean residence times are similar across species.…”
Section: Discussionsupporting
confidence: 92%
“…30 When these data were reanalyzed and modeled using the same approach employed in the current study, the calculated half-lives and mean residence times, although slightly less, were comparable to our results (Landt unpublished results). Similar values were obtained by Hill et al using a dose that was approximately 1a1000 of those used in the current study and in the study by Cumin et al 31 The shorter calculated half-lives observed in these studies may simply be attributable Table 2 Pharmacokinetic characteristics of recombinant met-human leptin when administered intraperitoneally (10 mgag body weight) to C57BLa6J mice fed a normal diet (n 6) or a high-fat diet (n 8) Leptin pharmacokinetics B Ahre Ân et al to a shorter sampling period, and hence the terminal elimination phase was de®ned by a minimal number of later time points. It is clear from comparing several different studies, using doses ranging over at least three orders of magnitude, that the rates of elimination and mean residence times are similar across species.…”
Section: Discussionsupporting
confidence: 92%
“…The bound fraction of leptin can be as high as 80% in humans with a leptin receptor mutation due to binding of leptin to circulating leptin receptors (96). An additional pool of leptin is bound to tissue-binding sites and is likely to contribute to the maintenance of steady-state plasma leptin levels (99). Based on anatomic and functional data, it appears that leptin exerts its effects on energy balance mainly by acting in the brain.…”
Section: Leptin Transport and Sites Of Actionmentioning
confidence: 99%
“…The Fc-hLeptin fusion and PEGylated hLeptin were shown to have half-lives of 10 h in mice and 48 h in rat, respectively (41)(42)(43). Compared with the hGH-CDR3H-coil-Herceptin fusion, hLeptin-CDR3H-coil-Herceptin displays a reduced half-life, which is attributable in part to the different species used in the two PK studies, and may also be due to proteolytic degradation of the fusion protein in vivo (44).…”
Section: Resultsmentioning
confidence: 99%